Do Patients With Multiple Myeloma Enrolled in Clinical Trials Live Longer?. (December 2021) - Aung, Taing N.; Bickell, Nina A.; Jagannath, Sundar; Kamath, Geetanjali; Meltzer, Jeremy; Kunzel, Brian; Egorova, Natalia N.
Abstract : Objectives: Enrollment in clinical trials is thought to improve survival outcomes through the trial effect. In this retrospective observational cohort study, we aimed to discern differences in survival outcomes by clinical trial enrollment and race-ethnicity. Materials and Methods: Of 1285 patients receiving care for multiple myeloma at an National Cancer Institute designated cancer center from 2012 to 2018, 1065 (83%) were nontrial and 220 (17%) were trial participants. Time to event analyses were used to adjust for baseline characteristics and account for clinical trial enrollment as a time-varying covariate. We analyzed propensity-matched cohorts of trial and nontrial patients to reduce potential bias in observational data. Results: Trial patients were younger (mean age in years: 60 vs. 63; P <0.001), underwent more lines of therapy (treatment lines ≥6: 39% vs. 17%; P <0.001), and had more comorbidities than nontrial patients. After controlling for baseline characteristics and clinical trial enrollment as a time-varying covariate, no significant difference in survival was found between trial and nontrial participants (hazard ratio [HR]=1.34, 95% confidence intervals [CIs]: 0.90-1.99), or between propensity-matched trial and nontrial participants (205 patients in each cohort, HR=1.36, 95% CIs: 0.83-2.23). Subgroup analyses by lines of therapy confirmed results from overall analyses. We did not observe survival differences by race-ethnicity (Logrank P =0.09), though hazard of death was significantly increased for nontrial Black/Hispanic patients compared with trial White patients (HR=1.76, 95% CIs=1.01-3.08). Conclusions: This study did not find evidence of a significant survival benefit to trial enrollment among patients with multiple myeloma. Patients enrolled in clinical trials underwent more lines of therapy, suggesting they may have had more treatment-resistant cancers. A small survival benefit in this cohort may be obscured by the lack of difference in survival between trial and nontrial patients. Abstract : Supplemental Digital Content is available in the text.